Sexual satisfaction and binge eating behaviors: correlation study - Pereira, Filomena (2017)
As basic human needs, diet and sexuality depend on the connections of multiple systems (muscular, neuro-endocrine, metabolic and reproductive), as well as aspects related to emotions, feelings and pleasure. Methods: A transversal, exploratory and quantitative, descriptive and correlational study. The instruments for data collection were the following: a questionnaire to describe the participants, the Index of Sexual Satisfaction (ISS) and the Binge Eating Scale (BES), both of which were translated and adapted to the Portuguese population. The statistical analysis was carried out with the statistics software program SPSS, version 23. Results: The results of the descriptive analysis show a sample of 306 patients, of which 69.3% are female and 30.7% are male, witb ages ranging from 18 to 64 years old. The study shows that the Binge Eating Scale (BES) is divided into three levels, with 219 respondents (71.6% of the sample) who are non-binging, followed by 49 patients (16% of the sample) with moderate binge and finally, in smaller numbers, 38 patients (12.4% of the sample) with severe binging. Furthermore, the study shows that even those with a BMI in the healthy weight range (4.5% and 1.5% in this category) show a moderate BES and a severe BES respectively.The correlational analysis confirmed the existence of a statistically significant (p ,205; α ,000) positive correlation between the sexual satisfaction of the sample and lhe level of binge eating. Furthermore, there was a highly significant statistical correlation between the BES, ISS and BMI variables, with a triangulation effect. Conclusion; This study demonstrates that people with normal weight or with an apparently "normal" profile can in fact show binge eating behaviors. In the study related to the level of Sexual Satisfaction (SS) of patients on difterent scales ofthe Boáy Mass Index (IMC), lhe average rate of ISS increases with the degree of obesity, indicating that these groups are dissatisfied with their sexuality, which increases with the level of BMI.